Exploring postoperative nasal airflow dynamics and impact on crust formation and mucosal healing after endoscopic tumor resection using computational fluid dynamics analysis - Yang Na; Minhae Park; Yong Gi Jung (PLoS ONE, 2025)
Background Postoperative observations in patients undergoing radical endoscopic resection surgery for sinonasal tumors have frequently noted the occurrence of mucosal crusts or bleeding on the nasal epithelial surface. This study employs computational fluid dynamics (CFD) techniques to elucidate the critical fluidic factors associated with these postoperative morbidities. Methods Three-dimensional models of the postoperative nasal cavities were constructed using thin-section computed tomography data from nine patients who underwent radical resection surgery for sinonasal tumors, encompassing endoscopic medial maxillectomy (N = 3), endoscopic craniofacial resection (N = 3), and endoscopic resection with septectomy (N = 3). Simulations of inspiratory airflow, assuming turbulent flow, were conducted to analyze airflow and air conditioning characteristics at sites where crust formation occurred. Results Frequent sites of crusting or bleeding were associated with the maxillary or sphenoidal sinuses (five out of nine subjects), where the ostia were substantially enlarged due to the surgery. Two distinct fluid dynamic features contributing to crust formation were identified. In five cases, crusts formed where local wall shear stress was elevated, while in four cases, crusts were observed in regions characterized by stagnant flow. Additionally, the relative humidity in the nasopharynx decreased to an unsatisfactory range (83.8‒85.7%). Conclusion This study demonstrated that two distinct fluid dynamic environments conducive to postoperative crust formation are possible, indicating that the wall shear stress level alone is insufficient for crust formation. Additionally, impaired humidification function observed following the surgery underscores the necessity of providing adequate moisturization for post-surgical care.